The basic criteria for the provision of affordable housing in Melaka - Mohamed Osman, Mariana; Ab Rahman, Syakir Amir; Ibrahim, Mansor (Malaysian Institute of Planners, 2018)
The aim of this paper is to examine the criteria in the selection of the houses by the homebuyers in Melaka. The case study area was selected from Melaka in response to the report produced by Khazanah Research Institutes (KRI) in 2015 that claims Melaka is the most affordable state in Malaysia. This study applies the quantitative approach. The Yamane Taro 1976 sampling formula was used and 400 samples were selected. Three types of analysis techniques was utilized namely descriptive analysis, Pearson correlation and Relative Importance Index RII). The study found that the three districts in Melaka were at affordable range for 2012 and 2014 and the income level of the household in Melaka was within the average income of Malaysia. Finally, it is anticipated that the study would give a clear picture on what are main criteria of better housing provision in Malaysia.